Financial and Strategic Analysis of Potential M&A Targets in the Indian Water Industry - Rajaram, Ganesan (2012)
Metito Utilities Limited (MUL) is a Middle East based Water Treatment Company with a growth rate of 20% CAGR. The company‟s vision is to become a leading player in water and wastewater industry in emerging markets, such as: India, China and Africa. Metito specifically aspires to be a $700 million company and have a diversified risk and market share in developing nations within a span of five years. The company is keen on abiding by its vision and is looking for a potential acquisition target in India with a turnover of >US$ 50 million (Metito Business Plan, 2012).